Increasing Brand Awareness: Health Knowledge, Environmental Focus and Green Innovation - Putri, Yulia Hamdaini; mavilinda, hera febria; Kumalasari, Farida (Universitas Islam Kadiri, 2024)
This study's objective is to establish, evaluate, and advance health information that can serve as a mediator between green innovation, brand awareness, and an environmental focus. The nature of this investigation is causal. Each individual in the sample was 200. Using SEM (partial least squares), the data was processed (PLS). Health Knowledge (X3), Environmental Focus Variable (X1), and Green Innovation (X2) all have an effect on brand awareness, according to the findings of this study (Y). Nevertheless, the impact of the health knowledge variable (X3) as a mediating factor between environmental focus (X1) and brand awareness (Y) is non-significant. With the intention of increasing customer brand awareness for green firms, this research suggests that business professionals should be guided toward environmentally focused initiatives and green innovation. A corporation or organization can encourage consumers to utilize itself by gaining greater recognition from them through the promotion of brand awareness.